2008
DOI: 10.1002/jms.1461
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and experimental study of tropylium formation from substituted benzylpyridinium species

Abstract: Fragmentation pathways of unsubstituted and substituted benzylpyridinium compounds were investigated using mass-analysed kinetic energy (MIKE) technique in combination with high level of quantum chemical calculations in the gas phase. Fast atom bombardment (FAB) source was used for ionisation of the studied compounds. The formation of both benzylium and tropylium species were investigated. Hybrid Hartree-Fock/Density Functional Theory calculations have been performed to assess the geometries and the energies o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
48
1
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 33 publications
3
48
1
1
Order By: Relevance
“…3). The fragments observed in these experiments have been observed previously [34,36,37] and presumably result from reaction pathways other than the simple loss of a neutral pyridine including intramolecular rearrangements [37] and rearrangement to the tropylium cation [28,38,39]. The peak at m/z 80.1 is assigned to [pyridine+H + ] + .…”
Section: Resultssupporting
confidence: 64%
“…3). The fragments observed in these experiments have been observed previously [34,36,37] and presumably result from reaction pathways other than the simple loss of a neutral pyridine including intramolecular rearrangements [37] and rearrangement to the tropylium cation [28,38,39]. The peak at m/z 80.1 is assigned to [pyridine+H + ] + .…”
Section: Resultssupporting
confidence: 64%
“…It is noteworthy that the ion at m/z 91 here should be benzyl cation. Previous theoretical studies suggested that conversion of the benzyl cation to the tropylium ion must surmount a significant energy barrier (65.0 kcal mol −1 [30], 67.8 kcal mol −1 [31]), so this process was usually not considered to occur in ESI mass spectrometry [32,33] though rare exceptions had been reported in the fragmentations of some benzylpyridinums [34][35][36]. For the occurrence of intra-complex reaction, INC-1 should have suitable amount of internal energy, which is enough for further reaction between the ion and the neutral species but not enough for direct separation.…”
Section: Fragmentation Of Protonated Nn′-dibenzylpiperazinementioning
confidence: 99%
“…In electrospray ionization mass spectrometry (ESI-MS), fragmentation of benzylated cations prefers to generate benzyl cations [7,8,[20][21][22][23][24][25][26][27][28][29][30], though a few exceptions have been reported that tropylium ion can be co-produced in the fragmentation of benzylpyridinium ions [18,31,32]. Besides the formation of benzyl cations, other interesting ions resulting from hydride transfer [24,25] or electrophilic aromatic substitution reactions [20][21][22] via the nonconventional ion/neutral complex (INC) can also be generated in the dissociation of benzylated cations.…”
Section: Introductionmentioning
confidence: 99%